Question
upstudy study bank question image url

Find the general solution to the system corresponding to the following matrix. \[ A=\left[\begin{array}{llll|l}1 & 7 & 0 & 0 & 2 \\ 0 & 0 & 1 & 3 & 4 \\ 0 & 0 & 0 & 0 & 0\end{array}\right] \] \( \left[\begin{array}{l}x_{1} \\ x_{2} \\ x_{3} \\ x_{4}\end{array}\right]=\left[\begin{array}{ll}\text { Ex: 1-2x_3 } \\ \square & \\ \square\end{array}\right] \) Enter \( 1-2 x_{3} \) as: \( 1-2 \times 3 \)

Ask by Long Washington. in the United States
Feb 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The general solution is: \[ \begin{cases} x₁ = 2 - 7s \\ x₂ = s \\ x₃ = 4 - 3t \\ x₄ = t \end{cases} \] where \( s \) and \( t \) are any real numbers.

Solution

We are given the augmented matrix   [1 7 0 0 | 2]   [0 0 1 3 | 4]   [0 0 0 0 | 0] which corresponds to the system of equations:   (1) x₁ + 7x₂ = 2   (2) x₃ + 3x₄ = 4   (3) 0 = 0 Note that x₁ and x₃ are leading variables, and x₂ and x₄ are free parameters. Let   x₂ = s   and  x₄ = t,  where s, t ∈ ℝ. Now solve for x₁ and x₃:   From (1): x₁ = 2 - 7s   From (2): x₃ = 4 - 3t Thus, the general solution to the system is   x₁ = 2 - 7s   x₂ = s   x₃ = 4 - 3t   x₄ = t Or, equivalently, in vector form:   [x₁, x₂, x₃, x₄]ᵀ = [2, 0, 4, 0]ᵀ + s[–7, 1, 0, 0]ᵀ + t[0, 0, –3, 1]ᵀ. This is the general solution to the given system.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To extract the general solution from the provided augmented matrix, we rewrite the system of equations represented by the matrix. The first equation gives us \( x_1 + 7x_2 = 2 \), and the second equation reveals \( x_3 + 3x_4 = 4 \). The third row, being all zeros, indicates that we have a free variable situation. Let's express \( x_2 \) and \( x_4 \) in terms of the free variable \( x_3 \). From the first equation, we isolate \( x_1 \): \[ x_1 = 2 - 7x_2 \] Then, from the second equation, solving for \( x_4 \): \[ x_4 = \frac{4 - x_3}{3} \] The complete representation of the solution is incorporated with arbitrary parameters. We can express the general solution in terms of \( x_3 \) and a free variable indicating \( x_2 \): \[ \begin{pmatrix} x_1 \\ x_2 \\ x_3 \\ x_4 \end{pmatrix} = \begin{pmatrix} 2 - 7x_2 \\ x_2 \\ x_3 \\ \frac{4 - x_3}{3} \end{pmatrix} \] Thus, the full solution involving substitutions can be packaged neatly. To finalize: 1. \( x_1 = 2 - 7 \times x_2 \) 2. \( x_2 = x_2 \) (free variable) 3. \( x_3 = x_3 \) (free variable) 4. \( x_4 = \frac{4 - x_3}{3} \) Expressing \( x_1 \): \[ \left[ \begin{array}{c} x_1 \\ x_2 \\ x_3 \\ x_4 \end{array} \right] = \left[ \begin{array}{c} 2 - 7x_{2} \\ x_{2} \\ x_{3} \\ \frac{4 - x_{3}}{3} \end{array} \right] \] This gives you the framework to define \( x_2 \) and \( x_3 \) freely!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy